PLAN DE NEGOCIOS PARA PRODUCTOS TURISTICOS EN LA FINCA “LOS RIOFRÍO” DE LA PARROQUIA TIMBARA, CANTÓN ZAMORA - RIOFRÍO ANDRADE, MARÍA FERNANDA (2019)
Ecuador has innumerable areas of great tourist attraction that stand out for their varied culture and great biodiversity, among these, the central mountains and the Amazon, present a great wealth. The need to carry out the present investigation is because, despite the privileged location of the "Los Riofrío" farm, it still has not been developed touristically, this is due to a lack of adequate infrastructure, which is why this proposal is carried out a "Business Plan for tourist products in the Finca" Los Riofrío "Parroquia Timbara, in Cantón Zamora. For the development of the research, a general objective was determined: "Prepare a Business Plan for tourist products in the Finca" Los Riofrío "Timbara parish, in Canton Zamora", also set specific objectives: Make a diagnosis of the current situation of the "Los Riofrío" farm; in which the internal situation of the farm and the entire area of influence was analyzed through different methods. Propose a Business Plan for tourism products in the "Los Riofrío" farm in which the definition of the business was developed; market study, technical study, business organization and financial study. Propose the strategies for the implementation of the Business Plan for tourism products in the "Los Riofrío" farm, in order to achieve the feasibility of the project. The inductive, deductive, analytical, and descriptive methods were used, with which all the field information was analyzed; Likewise techniques such as the survey and the interview, Karla Ricaurte's matrix and direct observation, the inventory and summary files of the Ministry of Tourism were also used; the same ones that allowed us to elaborate the SWOT Matrix, which allowed us to know the real situation facing the farm, after this the MEFE Matrix and the MEFI matrix were developed, which are in charge of the internal and external analysis to be able to establish the strategies to design the proposal. For the development of this research topic, the business plan was divided into five four studies: market study where the supply and demand analysis of the project was carried out, the strategic objective of promotion and dissemination of the project was also elaborated. estate; in the technical study the installed and used capacity was determined; the following strategic objectives were developed, to implement infrastructure for tourist services, to train the human talent of the farm; In addition, in this study, process diagrams were designed for the guidance service, in the administrative study the legal structure was elaborated. In terms of what the financial study has to do with the results obtained from both the internal and external analysis of the farm, the same was the basis for the proposal of the Business Plan, for which it was determined that the investment Initial for the execution of the project is $ 26,883,45; the execution of the project is feasible and feasible since the project is 5 years old and its period of recovery of capital will be 1 year 5 months, concluding 5 in this way that the Finca "Los Riofrío" has special characteristics to develop the activity tourism, that is, an environment where tourists can breathe the tranquility of the countryside and thus learn more about the production of the cane and all the products offered by the farm. After finishing the investigative work it is concluded that the farm is a place that has tourist resources conducive to create a different tourism alternative, also determined that the business plan for tourism products in the farm "The Riofrío" from a point From a technical, administrative and financial perspective, it is profitable and viable. For this reason its owner is recommended to execute the project, and in the same way to public and private institutions in conjunction with the Parish GAD support the initiative of small businesses in each undertaking and initiative to create new spaces and thus generate new income and sources of employment.